Future research directions for understanding the interconnections between climate change, water scarcity, and mobility in rural Central Asia - Hermans, K.; Djanibekov, N.; Abdullaev, Iskandar; Abduvalieva, N.; Assubayeva, A.; Blondin, S.; Bobojonov, I.; Conrad, C.; Herzfeld, T.; Kansiime, J.; Kimsanova, B.; Laldjebaev, M.; et al. (Informa UK Limited, 2025)
Central Asia faces substantial water scarcity due to increasing water demand driven by rapid urbanization, population growth, economic development, and inefficiency of irrigated agriculture. These developments are compounded by the effects of climate change, such as rising temperatures, loss of glacier mass and increased frequency of extreme events, including droughts. The region’s escalating water scarcity is causing disputes and straining rural livelihoods. Moreover, these challenges drive migration, creating considerable societal impacts. However, these issues remain underexplored in climate change research, making the region a global blind spot in climate adaptation and migration studies. We advocate for innovative research pathways that scrutinize smallholder adaptation strategies, examine the nexus between climate change, water scarcity, and mobility, and investigate tensions and cooperation over water resources. We conclude by emphasizing that substantial investments in inter- and transdisciplinary collaboration, improved data availability and quality, and strengthening of research and institutional capacities are essential to advance interdisciplinary climate impact research in Central Asia. Such efforts are vital for addressing existing knowledge gaps and enhancing evidence-based policymaking to improve the region’s position in current and future debates on climate change and sustainable development.